Numerical Modeling on Blasting Stress Wave in Interbedding Rheological Rockmass for the Stability of the Main Shaft of Mine - Li, Shuai; Zheng, Chao; Zhao, Yong (Frontiers in Earth Science, 2022)
High rheological property and strong mining disturbance are prominent conditions in deep rock projects, and often present a coupled process to induce rockbursts, collapse and land subsidence. This paper aims to investigate the effect of surrounding rheological rockmass on the main shaft of mine with interbedding structure under coupled blasting stress wave condition. Based on elastic damage theory and the constitutive equation of rheological rockmass, considering the total strain rate in tensor form, a double-rock model was established. The model was then validated by comparing the numerical simulations with the test results. Matlab was used to develop the COMSOL software, allowing numerical simulation of the failure of shaft rock sequentially subjected to this complex loading path. The results from the rheology-impact numerical simulations show that the double-rock rheology was greatly affected by the dynamic disturbance. Under high creep stress and constant impact stress wave, the last failure of the double-rock with higher creep stress is more severe than that of double-rock with lower creep stress. The numerical simulation of the shaft in situ stress was used to predict the collapse of the rheological rockmass with interbedding structure. The preliminary results suggest that one contribution to this phenomenon is likely related to irreversible damage in the rock during the creep-disturbance process. Dynamic disturbance also promoted the failure of the rock near the interbedding structure, but also increased the strain and stress. This may reflect the initial compaction and elastic phase the rock near the interbedding structure related to the large compressive strength of the hard rock during the dynamic disturbance. The numerical results indicate that a circle-shaped spalling damage zone is prone to develop around the shaft with increased time. We discuss the reason for the decreased stress on point A2 near the interbedding structure of the shaft by visco-elastic theory. The results clearly showed insufficient stability of surrounding rockmass, thus the initial design of shaft is not reasonable. This study has important referential significance for main shaft design for similar mines.